KEDUDUKAN HUKUM HAK ATAS TANAH DALAM PERKAWINAN CAMPURAN - Rizky Amalia; Sri Setyadji (Gapenas Publisher, 2023)
Indonesian citizens have the right to own land rights. However, for Indonesian citizens who carry out mixed marriages, there are exceptions, namely that an agreement on the separation of assets must be made. So that in this study there are 2 (two) problem formulations, namely: 1. What is the legal position of land rights in mixed marriages? 2. Can land rights from mixed marriages have the status of property rights? This research is normative juridical research using 3 (three) approach methods, namely statutory approach, conceptual approach, and case approach. And the results of the study found that based on the Constitutional Court Decision Number 69/PUU-XIII/2015, an agreement on the separation of assets can be made at the time of marriage, before the marriage takes place, or while in a marriage bond. Then based on the provisions of Article 21 Law Number 5 of 1960 concerning Basic Regulations on Agrarian Principles juncto Article 3 Government Regulation of the Republic of Indonesia Number 103 of 2015 concerning Ownership of Residential or Residential Houses by Foreigners Domiciled in Indonesia, Indonesian Citizens who carry out Mixed marriages can have the same land rights as other Indonesian citizens who do not carry out mixed marriages, but this must be proven by an agreement on the separation of assets